Bureaucracy and development: case study of a state directorate - Hassan, Arif (Rajagiri College of Social Sciences, Kochi, India, 2006)
The paper discusses the case of a state directorate involved in the development sector of the economy. It examines the decision making process using a file on which decision was already taken. The analysis of the file movement and the comments made by all the functionaries suggested that the decision making process was extremely cumbersome. It involved too many steps and reflected that officers involved in the decision making process acted more mechanically than sensibly. The paper suggested that several steps in the file movement process were redundant and could be streamlined. This may speed up the process.